2006
DOI: 10.1128/jb.01837-05
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of the Obligately Intracellular Bacterium Ehrlichia canis Reveals Themes of Complex Membrane Structure and Immune Evasion Strategies

Abstract: Ehrlichia canis, a small obligately intracellular, tick-transmitted, gram-negative, ␣-proteobacterium, is the primary etiologic agent of globally distributed canine monocytic ehrlichiosis. Complete genome sequencing revealed that the E. canis genome consists of a single circular chromosome of 1,315,030 bp predicted to encode 925 proteins, 40 stable RNA species, 17 putative pseudogenes, and a substantial proportion of noncoding sequence (27%). Interesting genome features include a large set of proteins with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 63 publications
0
63
0
3
Order By: Relevance
“…A membrana externa de uma bactéria é responsável pela ligação entre o microrganismo e o hospedeiro, desempenhando um papel essencial na adesão à célula e na evasão da resposta imune do hospedeiro (Mavromatis et al 2006). As proteínas bacterianas que intercedem essas interações entre as diferentes espécies de riquétsias são alvos da resposta imune do hospedeiro e têm grande relevância no diagnóstico diferencial entre as espécies de riquétsias (Tjalsma et al 2008).…”
Section: Discussionunclassified
“…A membrana externa de uma bactéria é responsável pela ligação entre o microrganismo e o hospedeiro, desempenhando um papel essencial na adesão à célula e na evasão da resposta imune do hospedeiro (Mavromatis et al 2006). As proteínas bacterianas que intercedem essas interações entre as diferentes espécies de riquétsias são alvos da resposta imune do hospedeiro e têm grande relevância no diagnóstico diferencial entre as espécies de riquétsias (Tjalsma et al 2008).…”
Section: Discussionunclassified
“…AR act as mediators for a diverse range of protein-protein interactions and are found commonly in eukaryotic and viral proteins, but rarely in bacteria (Lux et al, 1990;Bork, 1993;Mosavi et al, 2004). Eukaryotic-like AR have been reported in obligate intracellular bacteria such as the a-proteobacteria Wolbachia pipientis (IturbeOrmaetxe et al, 2005) and Ehrlichia canis (Mavromatis et al, 2006), as well as in the g-proteobacteria Legionella pneumophila (Habyarimana et al, 2008) and Coxiella butnetii (Voth et al, 2009). The involvement of AR proteins in host-bacterial associations and survival of the bacteria inside other cells has been highlighted recently by a mutant study of L. pneumophila, which showed that lack of certain AR proteins cause a significant defect in intracelluar replication (Habyarimana et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding TRPs, including Ecaj_0472 (TRP95), were identified in the genome sequence of E. canis and previously reported (16). Oligonucleotide primers for the amplification of the E. chaffeensis TRP75 and E. canis TRP95 gene fragments were designed manually, or by PrimerSelect (Lasergene v8.1; DNAStar, Madison, WI) according to the sequences in GenBank (accession numbers U49426 and NC_007354, respectively) and synthesized (Sigma-Genosys, Woodlands, TX) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%